A general analysis of the impact of international collaboration on the citation indices of scientific publications from 60 institutions across five continents - IRAINE DUARTE; HELLEN G.G. SANTOS; MARCIO L. RODRIGUES (Anais da Academia Brasileira de Ciências)
Abstract Several studies suggest that international collaboration increases the impact of science. In this study, we selected 50 universities and 10 research institutes to analyze whether publications produced over a 10-year period would gain more visibility through the occurrence of international collaboration. To address this question, we selected the top 10 ranked universities in the world (2023), along with the top-ranked universities in Africa, Asia, Latin America, and Oceania. Additionally, we included 10 research institutes from different areas of the globe in our analysis. The percentage of publications including international collaboration varied widely among these institutions. Analysis of the average number of citations per publication, in addition to the determination of the field-weighted citation impact, confirmed that international collaboration resulted in higher citation indices. Our study employed approaches to partially quantify the influence of international collaboration on the impact of science, which could serve as the basis for scientific policies aimed at stimulating international partnerships and increasing scientific visibility.